Portfolio assessment and evaluation: Implications and guidelines for clinical nursing education - M.M. Chabeli (AOSIS, 2002)
With the advent of Outcomes-Based Education in South Africa, the quality of nursing education is debatable, especially with regard to the assessment and evaluation of clinical nursing education, which is complex and renders the validity and reliability of the methods used questionable. This paper seeks to explore and describe the use of portfolio assessment and evaluation, its implications and guidelines for its effective use in nursing education. Firstly, the concepts of assessment, evaluation, portfolio and alternative methods of evaluation are defined. Secondly, a comparison of the characteristics of the old (traditional) methods and the new alternative methods of evaluation is made. Thirdly, through deductive analysis, synthesis and inference, implications and guidelines for the effective use of portfolio assessment and evaluation are described.